(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: The anatomical fold on the front portion of the hard palate is known as the palatal rugae. They are distinct and do not change during life, making them perfect for use as an identification tool when other options are unavailable. The aim of our study is to determine gender differences in palatal rugae pattern among the Bengali population in Chattogram of Bangladesh. Materials and methods: A total of 200 Bengali male (100) and female (100) populations aged 18 years and above were studied. The data was assessed based on the Thomas and Kotze classification. The student’s t-test was used to compare all quantitative data. Results: Curved and straight type palatal rugae were significantly higher (p < 0.05, p < 0.001 respectively) in males than females. Wavy and circular type palatal rugae were higher in females than males and the difference was significant (p < 0.001, p < 0.05 respectively). The female exhibited a higher converging palatal rugae p > 0.05. The male exhibited a higher diverging palatal rugae p < 0.001. Conclusion: The Bengali population of Chattogram has a distinctive pattern and sexual diversity of palatal rugae. That can be used to reliably identify subjects and gender differences in the Bengali population. JCMCTA 2022 ; 33 (1) : 82-87